If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9 = 6x + -5x + -3 Reorder the terms: 9 = -3 + 6x + -5x Combine like terms: 6x + -5x = 1x 9 = -3 + 1x Solving 9 = -3 + 1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 9 + -1x = -3 + 1x + -1x Combine like terms: 1x + -1x = 0 9 + -1x = -3 + 0 9 + -1x = -3 Add '-9' to each side of the equation. 9 + -9 + -1x = -3 + -9 Combine like terms: 9 + -9 = 0 0 + -1x = -3 + -9 -1x = -3 + -9 Combine like terms: -3 + -9 = -12 -1x = -12 Divide each side by '-1'. x = 12 Simplifying x = 12
| 3w=-93 | | (6x^2-54)/(9x+27) | | x^3-2x+1+3-2x^2+x= | | 22m-43=19m+5 | | (-6i)(-4i)=-24 | | 5x-3-2x=-3 | | 24=-12w+15w-3 | | -15=4x-7x+3 | | -17=n-25 | | 7x+1+x=49 | | -5=x+22 | | 6x+8-5x=7-3 | | 2(x-1)1+x/2 | | 4cos^2(x)+4sin(x)-5=0 | | 8n-10+12n=30 | | 2x+100=150 | | 96=-3y+24 | | 55=6-2h | | 8+k/2.5=14 | | 1.5x=2.52 | | 1369000000=10n | | 6+2k=-12 | | 1369000000=10 | | -4(x+1)+2=8 | | 18c^4-9c^2+7c=0 | | sqr(4x+1)+1=40 | | 10-2(x-1)=8 | | 4x^3+12x^2+16x=0 | | -(-2v-6)=-3-5(v+8) | | -2(8u-7)+4u=2(u+6) | | 2/3(x-6)-1/3(x-3) | | -2(8u-7)+4v=2(v+6) |